Consumer Behavior of Thai Fruit in China - Cao, Tianjia; Phonvichai, Thanavath (Journal of Ecohumanism, 2025)
The aim of this study is to investigate the demand dynamics of Thai fruit in China, focusing on Chinese consumer demand behavior of Thai fruit. The investigator conducts a market survey in Guangxi, China, total of 501 valid questionnaires were collected. The findings showed that the price elasticity of demand for Thai fruit is 1.2, this indicates that the quantity demanded of Thai fruit is highly sensitive with respect to price changes, and it also found that Thai fruit is a normal good with an income elasticity of 0.99, suggesting that the demand for Thai fruits is a common good rather than luxury goods. Demand function regression model analyses of the survey data identified several key factors affecting the demand for Thai fruits, including price, personal income, consumer preference, fruit quality, fruit brand, advertising and fruit safety, these independent variables are significate impact on the demand for Thai fruit and they are supported the hypothesis. The survey provides valuable insights and recommendations into consumer demand behavior and potential growth opportunities for Thai fruit in the Chinese market.